Learning Disruption among Elementary School Children Caused by Mobile Digital Games: A Literature Analysis of Parenting and Teaching Challenges - Mustakim (Indonesian Journal of Education and Science, 2026)
The rapid proliferation of mobile digital games has introduced both opportunities and challenges for elementary education, as children increasingly integrate gaming into their daily routines and social interactions. This study investigates the extent to which mobile digital gaming disrupts learning among elementary school children and examines the associated challenges faced by parents and teachers in managing these activities. Employing a qualitative literature analysis, the research synthesizes findings from peer-reviewed journal articles and scholarly books published within the last ten years. Data were collected through systematic identification, screening, and extraction of relevant studies, followed by thematic content analysis to identify patterns in academic, behavioral, social, and cognitive impacts, as well as parenting and instructional challenges. The results reveal that excessive mobile gaming negatively affects attention spans, academic motivation, study habits, and adherence to school routines. Behavioral and social consequences include increased individualism, antisocial tendencies, and potential gaming addiction, while cognitive impacts encompass diminished problem-solving skills, decision-making, and executive functioning. Parents face difficulties in monitoring game usage, managing emotional pressures, and providing effective guidance, whereas teachers encounter challenges in adapting pedagogical strategies, maintaining classroom focus, and collaborating with families. The findings highlight the systemic nature of learning disruption caused by mobile gaming and emphasize the need for digital literacy, structured parental guidance, and home–school collaboration. The study contributes to understanding the interplay between digital media use, child development, and educational practice, offering insights for policies and strategies that promote balanced digital engagement, enhance learning outcomes, and support holistic development in elementary education.